A high reliability low temperature sintered copper slurry and its preparation method and application
By using high-reliability low-temperature sintered copper slurry in the third-generation semiconductor WBG material packaging, the thermal stress, lead pollution, connection thickness, and insufficient toughness in the package are solved, and high sintering strength, high thermal conductivity and high Reliable interconnection heads meet the connection material needs of WBG materials.
Patent Information
- Application Number
- CN202311742884.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-18
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-12-18
AI Technical Summary
The prior art has thermal stress problems, lead pollution problems, connection thickness, insufficient toughness, corrosion resistance, welding property deviation problems in the packaging of third-generation semiconductor WBG materials, and electromigration of low-temperature sintered nano silver paste There are problems such as long sintering time, low junction density, and high packaging cost.
A high reliability low temperature sintered copper slurry is provided, which is made of 0.5% to 5% by weight of titanium nitride whiskers, 10% to 25% by weight of organic carrier and ultrafine copper particles composition with a balance of surface modification. The interconnection head formed by low-temperature sintering has excellent sintering strength, high thermal conductivity, high reliability and low resistivity.
It realizes the interconnection head with high sintering strength, high thermal conductivity and high reliability under low temperature sintering conditions, meets the connecting material needs of the third generation WBG materials and reduces the packaging cost.
Smart Images

Figure BDA0004613629530000151 
Figure BDA0004613629530000161
Abstract
Description
Technical Field
[0001] The present application relates to the field of semiconductor packaging interconnection technology, and in particular to a high-reliability low-temperature sintered copper paste and a preparation method and application thereof. Background Art
[0002] As the working environment of power electronic devices is increasingly tending towards high frequency, high temperature, high power, strong radiation and high voltage, the first and second generation semiconductor materials can no longer meet the requirements. The newly introduced third generation semiconductor WBG materials such as silicon carbide SiC and gallium nitride GaN have the advantages of electron saturation drift velocity, larger insulation breakdown electric field, higher thermal conductivity, wider bandgap width, etc., which can meet the requirements of high frequency, high temperature, high power, strong radiation and high voltage usage scenarios, resulting in the third generation semiconductor WBG materials being widely used in the field of power electronic devices.
[0003] The current traditional power device packaging materials used in the packaging of third-generation semiconductor WBG materials will cause problems such as thermal stress, lead pollution, connection thickness, insufficient toughness, corrosion resistance, weldability deviation, and growth of brittle intermetallic compounds. For example, high-lead solder has the advantages of good wetting performance and mature technology, but it has the environmental problem of lead pollution. High-temperature alloy solder has the advantages of high service temperature and stable joint connection, but the zinc-based solder has the problems of poor corrosion resistance and high welding temperature, the gold-based solder has the problems of poor welding performance and high price, and the bismuth-based solder has the problems of poor thermal conductivity and high brittleness. Transient liquid phase diffusion welding has the advantages of low-temperature connection, high-temperature service, low price, and compatibility with existing welding processes, but it has the problems of insufficient joint thickness, insufficient joint toughness, and immature technology.
[0004] As a new type of connection material that replaces traditional connection materials, low-temperature sintered nano-silver paste has a very important impact on the development of electronic devices and circuits. Low-temperature sintered nano-silver paste has the advantages of low-temperature sintering, high-temperature service, excellent thermal conductivity and electrical conductivity, and has good development prospects and application prospects in the packaging of third-generation semiconductor WBG materials. However, low-temperature sintered nano-silver paste also has problems such as electromigration, long sintering time, low junction density, and high packaging cost. For this reason, the present application provides a high-reliability low-temperature sintered copper paste and a preparation method thereof. Summary of the invention
[0005] In order to solve the above technical problems, the present application provides a high-reliability low-temperature sintered copper slurry and a preparation method and application thereof.
[0006] The high reliability low temperature sintering copper paste provided in the present application is realized by the following technical solutions:
[0007] A high-reliability low-temperature sintered copper paste is made of the following raw materials in percentage by mass: 0.5wt% to 5wt% of titanium nitride whiskers, 10wt% to 25wt% of an organic carrier, and the balance being a surface-modified ultrafine copper particle composition; the organic carrier contains an organosilicon-modified epoxy resin, an organic solvent, a dispersant, a leveling agent, a curing agent, and a coupling agent; the surface-modified ultrafine copper particle composition at least includes ultrafine copper particles of surface-modified nanoclusters.
[0008] The interconnection joints obtained by low-temperature sintering of the high-reliability low-temperature sintered copper paste in this application have excellent sintering strength, high thermal conductivity, high reliability and low resistivity, which meet the connection material requirements of the third-generation wide-bandgap semiconductor WBG, and can realize the electrical, thermal and mechanical connection between the chip surface electrode and the circuit lining, and further meet the application requirements of silicon carbide devices or gallium nitride devices in industries such as electric vehicles, smart grids, and new energy.
[0009] Furthermore, the preparation method of the surface-modified nanocluster ultrafine copper particles is as follows: firstly, 3 to 6 parts of a particle size D 50 =1-3 micron spherical ultrafine copper powder, 3-6 parts of silver nitrate, and 240-300 parts of ethylene glycol are mixed at 300-600 rpm for 100-200 seconds, and then ultrasonically dispersed for 2-4 hours, the obtained dispersion is heated to 138-145° C. at a heating rate of 4-6° C. / min and kept warm for 20-30 minutes, cooled naturally to room temperature and then centrifuged, and the obtained solid is cleaned with deionized water to obtain ultrafine copper particles with surface modified nanosilver clusters; the particle size of the nanosilver clusters loaded on the surface of the obtained ultrafine copper particles with surface modified nanosilver clusters is 10-20 nm, and the shape of the conductive silver particles is spherical.
[0010] By adopting the above technical solution, the overall anti-oxidation performance and joint connection stability of the low-temperature sintered copper paste can be improved.
[0011] Furthermore, the preparation method of the surface-modified nanocluster ultrafine copper particles is as follows: 10 parts of a particle size D 50=1-3 micron spherical ultrafine copper powder, 1-2 parts of nanosilver with an average particle size of 20-80nm, 100 parts of distilled water, and 10-25 parts of ethanol are mixed at 300-600rpm for 300-600s, and then transferred to a planetary ball mill after being evenly mixed. The planetary ball mill uses tungsten carbide grinding beads with a diameter of 1-4mm, and high-purity argon is introduced to exhaust the air in the planetary ball mill. After pressurizing to 0.5-0.8MPa, it is ball milled at 800-1600rpm for 8-12h, and after the pressure is released to normal pressure, the obtained ball milling product is rinsed with distilled water and transferred to a beaker, and the obtained ball milling product is decompressed and filtered to obtain a solid powder. Finally, the obtained solid powder is washed with distilled water for at least three times, and the obtained solid powder is dried at 65-80°C for 4-12h to obtain the finished product of surface-modified nano-clustered ultrafine copper particles.
[0012] By adopting the above technical solution, the overall anti-oxidation performance and joint connection stability of the low-temperature sintered copper paste can be improved.
[0013] Furthermore, the preparation method of the surface-modified ultrafine copper particles with nanoclusters is as follows: first, a mixed solution containing nano silver ions is prepared, 30-50 parts of the nano silver ion mixed solution and 10 parts of a particle size D 50 =1 to 3 micron spherical ultrafine copper powder is mixed at 300 to 600 rpm for 300 to 600 s to obtain a dispersion, the obtained dispersion is filtered, washed, and dried to obtain a solid, the obtained solid is mixed with 100 parts of distilled water and 10 to 25 parts of ethanol at 300 to 600 rpm for 300 to 600 s, and then transferred to a planetary ball mill after mixing evenly. The planetary ball mill uses tungsten carbide grinding beads with a diameter of 1 to 4 mm, and high-purity argon is introduced to exhaust the air in the planetary ball mill. After pressurizing to 0.5 to 0.8 MPa, it is ball milled at 800 to 1600 rpm for 8 to 12 hours, and after the pressure is released to normal pressure, the obtained ball milling product is rinsed with distilled water and transferred to a beaker, and the obtained ball milling product is filtered under reduced pressure to obtain a solid powder, and finally the obtained solid powder is washed with distilled water at least three times, and the obtained solid powder is dried at 65 to 80 ° C for 4 to 12 hours to obtain the finished product surface modified nano clusters of ultrafine copper particles.
[0014] By adopting the above technical solution, the overall anti-oxidation performance and joint connection stability of the low-temperature sintered copper paste can be improved.
[0015] Furthermore, the preparation method of the nano silver ion mixed solution is as follows: firstly prepare silver acetate ammonia complex CH3COO(NH3)2Ag, then slowly dropwise add formic acid HCOOH to the prepared silver acetate ammonia complex CH3COO(NH3)2Ag, wherein the mass ratio of formic acid HCOOH to silver acetate ammonia complex CH3COO(NH3)2Ag is (18-20): (65-70), and the mixture is added dropwise while stirring, and the stirring speed is 1000 -1500r / min, after the formic acid HCOOH is added, stirring is continued for 30-60min and then aged for 12-24h, the resulting mixed solution is heated to 120-150°C at a heating rate of 4-6°C / min and kept warm for 30-60min, and naturally cooled to room temperature to obtain a nano silver ion mixed solution, the obtained nano silver ion mixed solution contains spherical conductive nano silver particles, and the particle size distribution of the obtained spherical conductive nano silver particles is 2-20nm.
[0016] By adopting the above scheme, the overall anti-oxidation performance and joint connection stability of the low-temperature sintered copper paste can be further improved.
[0017] Furthermore, the surface-modified ultrafine copper particle composition at least includes ultrafine copper particles with surface-modified nanoclusters and single-atom modified graphene powder, the single-atom modified graphene powder accounts for 0.1wt% to 1.0wt% of the total mass of the surface-modified ultrafine copper particle composition, and the single-atom modified graphene powder includes a graphene carrier and a transition metal single atom loaded on the surface of the graphene carrier; the mass ratio of the transition metal single atom to the graphene carrier is 1:(10-50); the transition metal single atom is at least one of Cu and Ag.
[0018] By adopting the above scheme, the overall anti-oxidation performance and joint connection stability of the low-temperature sintered copper paste can be further improved, which is conducive to further improving the overall electrical conductivity and thermal conductivity of the low-temperature sintered copper paste.
[0019] Furthermore, the surface-modified ultrafine copper particle composition at least includes ultrafine copper particles with surface-modified nanoclusters, single-atom modified graphene powder and PDA@GNP-conductive nanosilver particles, and the PDA@GNP-conductive nanosilver particles account for 0.5wt% to 5wt% of the total mass of the surface-modified ultrafine copper particle composition.
[0020] By adopting the above scheme, the overall anti-oxidation performance and joint connection stability of the low-temperature sintered copper paste can be further improved, which is conducive to further improving the overall electrical conductivity and thermal conductivity of the low-temperature sintered copper paste.
[0021] Furthermore, the surface of the titanium nitride whisker is fixedly connected with carbon nanotubes CNTs through a connecting material, and the connecting material is a nanosilver sintered body; the preparation method of the titanium nitride whisker surface comprises the following steps: S1: preparing an Ag(2E4MI)2Ac complex solution; S2, adding polyvinyl pyrrolidone PVP and CNTs to the Ag(2E4MI)2Ac complex solution, wherein the mass ratio of the polyvinyl pyrrolidone PVP to the CNTs is 1:(0.8-1.2), and the mass ratio of the Ag(2E4MI)2Ac complex solution to the polyvinyl pyrrolidone PVP is (350-500):1, Then, ultrasonic dispersion is performed for 4-6 hours to add matrix titanium nitride whiskers, wherein the diameter of the matrix titanium nitride whiskers is 0.5-1.0um, the length is 10-20um, and the mass ratio of the titanium nitride whiskers to polyvinyl pyrrolidone PVP is (8-12):1. After the addition of the titanium nitride whiskers, ultrasonic dispersion is performed for 1-2 hours to obtain a dispersion; S3, the obtained dispersion is subjected to reduced pressure distillation to remove the organic solvent in the Ag(2E4MI)2Ac complex solution, and the obtained solid is subjected to high-temperature sintering treatment, the sintering temperature is 200-220°C, the obtained solid is crushed, dispersed in ethanol, ground, filtered, and dried to obtain the finished titanium nitride whiskers.
[0022] By adopting the above technical scheme, the overall anti-oxidation performance and joint connection stability of the low-temperature sintered copper paste can be further improved, which is conducive to further improving the overall electrical conductivity and thermal conductivity of the low-temperature sintered copper paste. In addition, the sintering temperature can be reduced, and the prepared interconnection joints can be improved to have better shear strength, Young's modulus and toughness.
[0023] The present application provides a method for preparing a high-reliability low-temperature sintered copper paste, which is achieved by the following scheme:
[0024] A method for preparing a high-reliability low-temperature sintered copper slurry comprises the following steps:
[0025] Step 1, preparation of ultrafine copper particles with surface-modified nanoclusters, and configuration of a prefabricated organic carrier, wherein the prefabricated organic carrier does not contain a curing agent;
[0026] Step 2: subjecting the surface-modified nanocluster ultrafine copper particles to ultrasonic dispersion treatment with a 4-8 g / L coupling agent aqueous solution for 0.5-2 h, draining, and low-temperature drying to obtain surface-modified nanocluster ultrafine copper particles;
[0027] Step three, add the surface-modified nanoclusters of ultrafine copper particles and titanium nitride whiskers treated by surface modification in step 2 to the prefabricated organic carrier prepared in step one at a rate of 0.5-2.0 g / s, stirring while adding, and the stirring speed is 60-120 r / min. After the addition is completed, add a curing agent and stir for 5-10 minutes while maintaining a speed of 60-120 r / min to obtain a high-reliability low-temperature sintered copper slurry.
[0028] The preparation method provided in this application is relatively simple, has low operating difficulty, and is easy to implement industrial production.
[0029] A high-reliability, low-temperature sintered copper paste is used in semiconductor packaging interconnection materials in the electronics industry, especially in packaging interconnection material electronic paste for third-generation semiconductor WBG materials, to achieve electrical, thermal and mechanical connection between chip surface electrodes and circuit linings, meeting the application needs of silicon carbide devices or gallium nitride devices in industries such as electric vehicles, smart grids, and new energy.
[0030] In summary, this application has the following advantages:
[0031] 1. The interconnection joint obtained by low-temperature sintering in this application has excellent sintering strength, high thermal conductivity, high reliability and low resistivity, meeting the connection material requirements of the third-generation wide bandgap semiconductor WBG.
[0032] 2. The preparation method provided in this application is relatively simple, has low operating difficulty, and is easy to implement industrial production.
[0033] 3. This application is applied to semiconductor packaging interconnection materials in the field of electronics industry, especially packaging interconnection material electronic paste of third-generation semiconductor WBG materials, to achieve electrical, thermal and mechanical connection between chip surface electrodes and circuit substrates. DETAILED DESCRIPTION
[0034] In order to further understand the technical creativity of the present application, the present application is technically explained below in combination with embodiments and comparative examples.
[0035] Example
[0036] A high-reliability, low-temperature sintered copper paste is used for semiconductor packaging interconnection materials in the electronics industry, especially for packaging interconnection electronic paste of third-generation semiconductor WBG materials, to achieve electrical, thermal and mechanical connection between chip surface electrodes and circuit linings.
[0037] A high-reliability low-temperature sintered copper paste is made of the following raw materials in percentage by weight: 0.5wt% to 5wt% of titanium nitride whiskers, 10wt% to 25wt% of an organic carrier, and the balance is a surface-modified ultrafine copper particle composition. The organic carrier contains an organosilicon-modified epoxy resin, an organic solvent, a dispersant, a leveling agent, a curing agent, and a coupling agent. The surface-modified ultrafine copper particle composition at least includes ultrafine copper particles with surface-modified nanoclusters.
[0038] There are three main methods for preparing ultrafine copper particles with surface modified nanoclusters:
[0039] The first method is to prepare the surface-modified nanocluster ultrafine copper particles as follows: first, 3 to 6 parts of a particle size D 50 =1-3 micron spherical ultrafine copper powder, 3-6 parts of silver nitrate, and 240-300 parts of ethylene glycol are mixed at 300-600rpm for 100-200s, and then ultrasonically dispersed for 2-4h, the obtained dispersion is heated to 138-145°C at a heating rate of 4-6°C / min and kept warm for 20-30min, naturally cooled to room temperature and then centrifuged, the obtained solid is cleaned with deionized water, and ultrafine copper particles with surface modified nanoclusters can be obtained; the particle size of the conductive silver particles loaded on the surface of the obtained ultrafine copper particles with surface modified nanoclusters is 10-20nm, and the shape of the conductive silver particles is spherical.
[0040] The second method for preparing the surface-modified nanocluster ultrafine copper particles is as follows: 10 parts of a particle size D 50 =1-3 micron spherical ultrafine copper powder, 1-2 parts of nanosilver with an average particle size of 20-80nm, 100 parts of distilled water, and 10-25 parts of ethanol are mixed at 300-600rpm for 300-600s, and then transferred to a planetary ball mill after being evenly mixed. The planetary ball mill uses tungsten carbide grinding beads with a diameter of 1-4mm. High-purity argon gas is introduced to exhaust the air in the planetary ball mill. After pressurizing to 0.5-0.8MPa, it is ball milled at 800-1600rpm for 8-12h. After the pressure is released to normal pressure, the obtained ball milling product is rinsed with distilled water and transferred to a beaker. The obtained ball milling product is decompressed and filtered to obtain a solid powder. Finally, the obtained solid powder is washed with distilled water for at least three times. The obtained solid powder is placed at 65-80°C and dried for 4-12h to obtain finished product surface-modified nano-cluster ultrafine copper particles.
[0041] The third method for preparing the surface-modified ultrafine copper particles with nanoclusters is as follows: first, prepare a mixed solution containing nano silver ions, take 30-50 parts of the nano silver ion mixed solution and 10 parts of a particle size D 50=1 to 3 micron spherical ultrafine copper powder is mixed at 300 to 600 rpm for 300 to 600 s to obtain a dispersion, the obtained dispersion is filtered, washed, and dried to obtain a solid, the obtained solid is mixed with 100 parts of distilled water and 10 to 25 parts of ethanol at 300 to 600 rpm for 300 to 600 s, and then transferred to a planetary ball mill after mixing evenly. The planetary ball mill uses tungsten carbide grinding beads with a diameter of 1 to 4 mm, and high-purity argon is introduced to exhaust the air in the planetary ball mill. After pressurizing to 0.5 to 0.8 MPa, it is ball milled at 800 to 1600 rpm for 8 to 12 hours, and after the pressure is released to normal pressure, the obtained ball milling product is rinsed with distilled water and transferred to a beaker, and the obtained ball milling product is filtered under reduced pressure to obtain a solid powder, and finally the obtained solid powder is washed with distilled water at least three times, and the obtained solid powder is dried at 65 to 80 ° C for 4 to 12 hours to obtain the finished product surface modified nano clusters of ultrafine copper particles.
[0042] The preparation method of the nano silver ion mixed solution is as follows: firstly prepare silver acetate ammonia complex CH3COO(NH3)2Ag, then slowly dropwise add formic acid HCOOH into the prepared silver acetate ammonia complex CH3COO(NH3)2Ag, wherein the mass ratio of the formic acid HCOOH to the silver acetate ammonia complex CH3COO(NH3)2Ag is (18-20):(65-70), the mixture is added dropwise while stirring, and the stirring speed is 1000-1500r / min. After the formic acid HCOOH is added dropwise, stirring is continued for 30-60min and then aged for 12-24h. The obtained mixed solution is heated to 120-150℃ at a heating rate of 4-6℃ / min and kept warm for 30-60min, and naturally cooled to room temperature to obtain the nano silver ion mixed solution. The obtained nano silver ion mixed solution contains spherical conductive nano silver particles, and the particle size of the obtained spherical conductive nano silver particles is 2-20nm.
[0043] Furthermore, the surface-modified ultrafine copper particle composition at least includes ultrafine copper particles with surface-modified nanoclusters and single-atom modified graphene powder, the single-atom modified graphene powder accounts for 0.1wt% to 1.0wt% of the total mass of the surface-modified ultrafine copper particle composition. The single-atom modified graphene powder includes a graphene carrier and a transition metal single atom supported on the surface of the graphene carrier, the mass ratio of the transition metal single atom to the graphene carrier is 1:(10-50), and the transition metal single atom is at least one of Cu and Ag.
[0044] Furthermore, the surface-modified ultrafine copper particle composition includes at least ultrafine copper particles with surface-modified nanoclusters, single-atom modified graphene powder and PDA@GNP-conductive nanosilver particles, and the PDA@GNP-conductive nanosilver particles account for 0.5wt% to 5wt% of the total mass of the surface-modified ultrafine copper particle composition.
[0045] The surface of the titanium nitride whisker is fixedly connected with carbon nanotubes CNTs through a connecting material, and the connecting material is a nanosilver sintered body. The preparation method of the titanium nitride whisker surface comprises the following steps:
[0046] S1: preparing Ag(2E4MI)2Ac complex solution;
[0047] S2, adding polyvinyl pyrrolidone PVP and CNTs to the Ag(2E4MI)2Ac complex solution, the mass ratio of polyvinyl pyrrolidone PVP to CNTs is 1:(0.8-1.2), the mass ratio of Ag(2E4MI)2Ac complex solution to polyvinyl pyrrolidone PVP is (350-500):1, then ultrasonically dispersing for 4-6 hours, adding matrix titanium nitride whiskers, the diameter of the matrix titanium nitride whiskers is 0.5-1.0um, the length is 10-20um, the mass ratio of titanium nitride whiskers to polyvinyl pyrrolidone PVP is (8-12):1, and after the addition of titanium nitride whiskers, ultrasonically dispersing for 1-2 hours to obtain a dispersion;
[0048] S3, the obtained dispersion is subjected to reduced pressure distillation to remove the organic solvent in the Ag(2E4MI)2Ac complex solution, and the obtained solid is subjected to high-temperature sintering treatment at a sintering temperature of 200-220°C. The obtained solid is crushed, dispersed in ethanol, ground, filtered, and dried to obtain finished titanium nitride whiskers.
[0049] A method for preparing a high-reliability low-temperature sintered copper slurry comprises the following steps:
[0050] Step 1, preparation of ultrafine copper particles with surface-modified nanoclusters, and configuration of a prefabricated organic carrier, wherein the prefabricated organic carrier does not contain a curing agent;
[0051] Step 2: subjecting the surface-modified nanocluster ultrafine copper particles to ultrasonic dispersion treatment with a 4-8 g / L coupling agent aqueous solution for 0.5-2 h, draining, and low-temperature drying to obtain surface-modified nanocluster ultrafine copper particles;
[0052] Step three, add the surface-modified nanocluster ultrafine copper particles and titanium nitride whiskers treated by surface modification in step two to the prefabricated organic carrier prepared in step one at a rate of 0.5-2.0 g / s, stir while adding, and the stirring speed is 60-120 r / min. After the addition is completed, add a curing agent and stir for 5-10 minutes while maintaining a speed of 60-120 r / min to obtain a high-reliability low-temperature sintered copper slurry, and sinter at 5-10 MPa and 200-240° C. to obtain an interconnecting material.
[0053] Example 1: A high-reliability low-temperature sintering copper paste is made of the following raw materials in percentage by mass: 0.5wt% titanium nitride whiskers (diameter 0.5-1.0um, length 10-20um, purchased from Zhejiang Yamei Nano Technology Co., Ltd., model: AM-TiN-W-01), 14.5wt% organic carrier, and 85wt% surface-modified nanocluster ultrafine copper particles.
[0054] The organic carrier is composed of 100 parts of silicone modified epoxy resin TY-H26 (Green Union (Jining) Chemical Technology Co., Ltd.), 40 parts of organic solvent DMF, 25 parts of acetone, 2 parts of dispersant - BASF Efka FA 4650, 3 parts of leveling agent - BYKRHEOBYK 410 liquid rheological additive, 2 parts of curing agent - dicyandiamide, 1.2 parts of curing agent - maleic anhydride, and 1 part of coupling agent - KH560.
[0055] A high reliability low temperature sintering copper paste comprises the following steps:
[0056] Step 1, preparation of ultrafine copper particles with surface modified nanoclusters;
[0057] First, 5g of particle size D 50 =1-3 micron spherical ultrafine copper powder, 5g of silver nitrate, and 300mL of ethylene glycol are mixed at 500rpm for 200s, and then subjected to ultrasonic dispersion treatment for 4h, with an ultrasonic power of 400W and an ultrasonic frequency of 44kHz. The obtained dispersion is heated from room temperature to 140°C at a heating rate of 5°C / min and kept warm for 30min, cooled naturally to room temperature and then centrifuged, and the obtained solid is cleaned with deionized water to obtain ultrafine copper particles with surface modified nanoclusters; the particle size of the surface-loaded conductive silver particles is 10-20nm, and the shape of the conductive silver particles is spherical;
[0058] At the same time, the organic carrier was prepared by mixing 100g of organosilicon-modified epoxy resin TY-H26, 40g of organic solvent DMF, 25g of acetone, 2g of dispersant-BASF Efka FA 4650, 3g of leveling agent-BYK RHEOBYK 410 liquid rheological additive, and 1g of coupling agent-KH560;
[0059] Step 2: subjecting the surface-modified nanocluster ultrafine copper particles to ultrasonic dispersion treatment with a 6 g / L KH560 coupling agent aqueous solution for 1 h, with an ultrasonic power of 400 W and an ultrasonic frequency of 44 kHz, and then draining and low-temperature drying to obtain surface-modified nanocluster ultrafine copper particles;
[0060] At the same time, the titanium nitride whiskers and the 6g / L KH560 coupling agent aqueous solution were subjected to ultrasonic dispersion treatment for 1 hour, with an ultrasonic power of 400W and an ultrasonic frequency of 44kHz, and then the surface-modified titanium nitride whiskers were obtained after being drained and dried at low temperature.
[0061] Step three, add the surface-modified nanocluster ultrafine copper particles and surface-modified titanium nitride whiskers treated in step 2 to the prefabricated organic carrier prepared in step one at a rate of 0.5 g / s, stirring while adding, and the stirring speed is 60 r / min. After the addition is completed, 2 g of curing agent-dicyandiamide and 1.2 g of curing agent-maleic anhydride are added at a speed of 60 r / min, and stirring is continued for 5 minutes to obtain a high-reliability low-temperature sintered copper slurry, and sintering at 8 MPa and 240°C for 30 minutes can obtain an interconnecting material.
[0062] The difference between Example 2 and Example 1 is that a high-reliability low-temperature sintering copper paste is made of the following raw materials in percentage by weight: 2.5wt% of titanium nitride whiskers, 14.5wt% of organic carrier, and 83wt% of surface-modified nanocluster ultrafine copper particles.
[0063] The difference between Example 3 and Example 1 is that a high-reliability low-temperature sintering copper paste is made of the following raw materials in percentage by mass: 5wt% of titanium nitride whiskers, 14.5wt% of organic carrier, and 80.5wt% of surface-modified nanocluster ultrafine copper particles.
[0064] The difference between Example 4 and Example 1 is that a high reliability low temperature sintered copper paste is made of the following raw materials in mass percentage: 2.5wt% of modified titanium nitride whiskers, 14.5wt% of organic carrier, and 83wt% of surface modified nano-cluster ultrafine copper particles. The modified titanium nitride whiskers are formed by fixing carbon nanotubes CNTs on the surface of the titanium nitride whiskers as a base through a connecting material-nanosilver sintered body.
[0065] The method for preparing the surface of modified titanium nitride whisker comprises the following steps:
[0066] S1: Preparation of Ag(2E4MI)2Ac complex solution: at room temperature, add 0.02 mol of 2-ethyl-4-methylimidazole 2E4MI and 0.01 mol of silver acetate AgAc into 400 mL of dichloromethane, stir magnetically at a speed of 240 r / min, and control the magnetic stirring time to 1-2 hours until the AgAc particles completely disappear to obtain a clear and transparent Ag(2E4MI)2Ac complex solution;
[0067] S2, add 0.5g of polyvinyl pyrrolidone PVP and 0.5g of CNTs to the Ag(2E4MI)2Ac complex solution, and then perform ultrasonic dispersion for 4h, the power of the ultrasonic generator is 400W, the frequency is 44kHz, add 40g of matrix titanium nitride whisker, and after the addition of titanium nitride whisker, perform ultrasonic dispersion for another 1h, the power of the ultrasonic generator is 400W, the frequency is 44kHz, to obtain a dispersion;
[0068] S3, the obtained dispersion is subjected to reduced pressure distillation to remove the organic solvent - dichloromethane in the Ag(2E4MI)2Ac complex solution, and the obtained solid is subjected to high-temperature sintering treatment at a sintering temperature of 220°C. The obtained solid is crushed, dispersed in ethanol, ground, filtered, and dried to obtain the finished modified titanium nitride whiskers.
[0069] In the second step of preparing a high-reliability low-temperature sintered copper slurry: 5 g of the finished modified titanium nitride whisker is added to 1.0 L of a 6 g / L KH560 coupling agent aqueous solution, mechanically stirred at 120 rpm for 30 min, drained, and low-temperature dried to obtain surface-modified titanium nitride whiskers, and the other preparation steps are the same.
[0070] The difference between Example 5 and Example 4 is that the preparation method of the surface-modified ultrafine copper particles with nanoclusters is as follows: 10 g of particle size D 50 =1-3 micron spherical ultrafine copper powder, 2g of nanosilver with an average particle size of 20-80nm (superior product, model CB2311, Wuhan Lvjing Fenghua Biotechnology Co., Ltd.), 100g of distilled water, and 20mL of ethanol were mixed at 500rpm for 600s, and then transferred to a planetary ball mill after mixing evenly. The planetary ball mill used tungsten carbide grinding beads with a diameter of 2mm. High-purity argon was introduced to exhaust the air in the planetary ball mill, and the ball mill was pressurized to 0.8MPa and then ball-milled at 1500rpm for 12h. After the pressure was released to normal pressure, the obtained ball-milled product was rinsed with distilled water and transferred to a beaker. The obtained ball-milled product was filtered under reduced pressure to obtain a solid powder. Finally, the obtained solid powder was washed three times with distilled water, and the obtained solid powder was dried at 80°C for 8h to obtain the finished product of surface-modified nano-clusters of ultrafine copper particles.
[0071] The difference between Example 6 and Example 4 is that the method for preparing the ultrafine copper particles with surface modified nanoclusters comprises the following steps:
[0072] Step 1, preparing a mixed solution containing nano silver ions, as follows:
[0073] First, silver acetate ammonia complex CH3COO(NH3)2Ag was prepared by dissolving 32g of silver acetate (CH3COOAg) in 33g of ammonia water (NH3 mass content was 25%) to obtain silver acetate ammonia complex (CH3COO(NH3)2Ag); then 18g of formic acid HCOOH was slowly added dropwise (dropping speed 4mL / min) to the prepared silver acetate ammonia complex CH3COO(NH3)2Ag, while stirring at a stirring speed of 1500r / min, after the formic acid HCOOH is added dropwise, stirring is continued for 40min and then aged for 24h, the obtained mixed solution is heated to 130°C at a heating rate of 5°C / min and kept warm for 40min, and naturally cooled to room temperature to obtain a nano silver ion mixed solution, the obtained nano silver ion mixed solution contains spherical conductive nano silver particles, and the particle size distribution of the obtained spherical conductive nano silver particles is 2-20nm, that is, the conductive nano silver particles are relatively finer;
[0074] Step 2: Take 40g of nano silver ion mixture and 10g of particle size D 50 =1 to 3 micron spherical ultrafine copper powder is mixed at 500rpm for 600s to obtain a dispersion, the obtained dispersion is filtered, washed and dried to obtain a solid, the obtained solid is mixed with 100g of distilled water and 20mL of ethanol at 500rpm for 600s, and after mixing evenly, it is transferred to a planetary ball mill, which uses tungsten carbide grinding beads with a diameter of 2mm. High-purity argon is introduced to exhaust the air in the planetary ball mill, and the ball mill is pressurized to 0.8MPa and then ball-milled at 1500rpm for 12h. After the pressure is released to normal pressure, the obtained ball milling product is rinsed with distilled water and transferred to a beaker, and the obtained ball milling product is decompressed and filtered to obtain a solid powder. Finally, the obtained solid powder is washed with distilled water for at least three times, and the obtained solid powder is dried at 80°C for 8h to obtain finished surface-modified nanocluster ultrafine copper particles.
[0075] The difference between Example 7 and Example 6 is that the surface-modified ultrafine copper particle composition is composed of ultrafine copper particles with surface-modified nanoclusters and single-atom modified graphene powder. A high-reliability low-temperature sintered copper slurry is made of the following raw materials in percentage by mass: 2.5wt% titanium nitride whiskers, 14.5wt% organic carrier, 82.96wt% ultrafine copper particles with surface-modified nanoclusters, and 0.04wt% single-atom modified graphene powder.
[0076] The preparation method of single-atom doped graphene powder comprises the following steps:
[0077] S1, 0.4g of graphene (single-layer graphene nanosheet, model: AM-C3-065-1) and 200g of acetone aqueous solution (5wt% acetone) are stirred at 500rpm to form a graphene dispersion; at the same time, potassium hydroxide and deionized water form a 6.0wt% potassium hydroxide aqueous solution, and the graphene dispersion and the potassium hydroxide aqueous solution are added to a beaker at a mass ratio of 20:1, that is, 22g of 6.0wt% potassium hydroxide aqueous solution is added to the prepared graphene dispersion, and a glass rod is used to manually stir for 3min in advance, and the beaker is placed in an ultrasonic cleaning machine after standing for 5min, and ultrasonic dispersion treatment is performed for 60min, and vacuum filtration is performed after the ultrasonic dispersion treatment is completed, and the obtained powder is placed at 80-85°C for drying for 4h, and then placed in a planetary ball mill for ball milling treatment, the ball milling speed is 60rpm, and the ball milling time is 80min, to obtain an activated graphene mixed powder;
[0078] S2, 0.8 g of the activated graphene mixed powder prepared in S1 is loaded into crucible A;
[0079] 1.08 g of metal salt is loaded into crucible B: the metal salt is copper nitrate and silver nitrate, wherein the mass ratio of Cu in copper nitrate to Ag in nickel nitrate is 4:1. Crucible B is divided into two areas, and the area ratio of the two areas is 4:1. The copper nitrate is placed in the area with a larger area and spread evenly with a scraper, and the silver nitrate is placed in the area with a smaller area and spread evenly with a scraper, and the metal salt loading is completed;
[0080] Crucible A and crucible B are loaded into a sealed tube furnace, with crucible A located downstream of crucible B. Under the protection of Ar atmosphere, crucible A is heated to 600°C at 8.0°C / min and kept warm for 1.0h, and crucible B is heated to 750°C at 10°C / min and kept warm for 60min, to obtain a metal single atom-doped graphene precursor;
[0081] S3, the metal single atom doped graphene precursor was placed in a 0.1 mol / L dilute hydrochloric acid aqueous solution for ultrasonic cleaning for 60 min, the ultrasonic power was 740 W, the ultrasonic frequency was 44 kHz, and then vacuum filtered and washed with pure water until neutral, placed at 80 ° C for 12 h, and ball milled with a planetary ball mill at a speed of 60 rpm for 60 min to a particle size D 50 =500nm single-atom-doped graphene powder, in which the total content of copper and silver atoms is 3.87wt%.
[0082] The difference between Example 8 and Example 7 is that a high-reliability low-temperature sintered copper paste is made of the following raw materials in percentage by mass: 2.5wt% of titanium nitride whiskers, 14.5wt% of organic carrier, 82.9wt% of ultrafine copper particles of surface-modified nanoclusters, and 0.1wt% of single-atom modified graphene powder.
[0083] The difference between Example 9 and Example 7 is that a high-reliability low-temperature sintered copper paste is made of the following raw materials in percentage by mass: 2.5wt% of titanium nitride whiskers, 14.5wt% of organic carrier, 82.6wt% of ultrafine copper particles with surface-modified nanoclusters, and 0.4wt% of single-atom modified graphene powder.
[0084] The difference between Example 10 and Example 7 is that a high-reliability low-temperature sintered copper paste is made of the following raw materials in percentage by mass: 2.5wt% of titanium nitride whiskers, 14.5wt% of organic carrier, 82.17wt% of ultrafine copper particles with surface-modified nanoclusters, and 0.83wt% of single-atom modified graphene powder.
[0085] The difference between Example 11 and Example 7 is that a high-reliability low-temperature sintered copper paste is made of the following raw materials in percentage by mass: 2.5wt% of titanium nitride whiskers, 14.5wt% of organic carrier, 82wt% of ultrafine copper particles of surface-modified nanoclusters, and 1wt% of single-atom modified graphene powder.
[0086] The difference between Example 12 and Example 9 is that the surface-modified ultrafine copper particle composition consists of ultrafine copper particles with surface-modified nanoclusters, single-atom modified graphene powder and PDA@GNP-conductive nanosilver particles.
[0087] A high-reliability low-temperature sintering copper paste is prepared from the following raw materials in percentage by weight: 2.5wt% of titanium nitride whiskers, 14.5wt% of organic carriers, 82.42wt% of ultrafine copper particles of surface-modified nanoclusters, 0.4wt% of single-atom modified graphene powder, and 0.18wt% of PDA@GNP-conductive nanosilver particles.
[0088] The preparation method of PDA@GNP-conductive silver nanoparticles is as follows:
[0089] Step 1: Disperse 54 mg of graphene in 25 mL of dimethylformamide (DMF) to obtain a graphene suspension;
[0090] Step 2: Dissolve 150 mg of dopamine hydrochloride in 300 mL of Tris-HCl buffer (trishydroxymethylaminomethane), then adjust the pH value to 9 with 10% NaOH, add the graphene suspension obtained in step 1, heat and react at 60°C with 300 rpm magnetic stirring for 10 h, filter, wash with deionized water 3 times, and dry at 80°C for 24 h to obtain PDA@GNP nanoparticles;
[0091] Step three, dissolve 1.02g of silver nitrate in 40mL of deionized water, add ammonia water until the solution is clarified again, then dissolve 1.2g of polyvinylpyrrolidone PVP in silver ammonia solution (i.e., ammonia solution of silver nitrate), add 40mg of GNP@PDA nanoparticles obtained in step two, and then heat the reaction at 60°C under magnetic stirring for 5.0h. After the reaction is completed, centrifuge and wash to obtain PDA@GNP-conductive nanosilver particles.
[0092] The difference between Example 13 and Example 12 is that the high-reliability low-temperature sintering copper paste is made of the following raw materials in percentage by mass: 2.5wt% of titanium nitride whiskers, 14.5wt% of organic carrier, 82.18wt% of surface-modified nanocluster ultrafine copper particles, 0.4wt% of single-atom modified graphene powder, and 0.42wt% of PDA@GNP-conductive nanosilver particles.
[0093] The difference between Example 14 and Example 12 is that the high-reliability low-temperature sintering copper paste is made of the following raw materials in percentage by mass: 2.5wt% of titanium nitride whiskers, 14.5wt% of organic carrier, 80.3wt% of surface-modified nanocluster ultrafine copper particles, 0.4wt% of single-atom modified graphene powder, and 2.3wt% of PDA@GNP-conductive nanosilver particles.
[0094] The difference between Example 15 and Example 12 is that the high-reliability low-temperature sintering copper paste is made of the following raw materials in percentage by mass: 2.5wt% of titanium nitride whiskers, 14.5wt% of organic carrier, 78.6wt% of surface-modified nanocluster ultrafine copper particles, 0.4wt% of single-atom modified graphene powder, and 4wt% of PDA@GNP-conductive nanosilver particles.
[0095] The difference between Example 16 and Example 12 is that the high-reliability low-temperature sintering copper paste is made of the following raw materials in percentage by mass: 2.5wt% of titanium nitride whiskers, 14.5wt% of organic carrier, 77.6wt% of surface-modified nanocluster ultrafine copper particles, 0.4wt% of single-atom modified graphene powder, and 5wt% of PDA@GNP-conductive nanosilver particles.
[0096] The difference between Comparative Example 1 and Example 1 is that a high-reliability low-temperature sintering copper paste is made of the following raw materials in percentage by weight: 14.5 wt % of an organic carrier and 85.5 wt % of ultrafine copper particles with surface-modified nanoclusters.
[0097] The difference between Comparative Example 2 and Example 1 is that a high-reliability low-temperature sintering copper paste is made of the following raw materials in percentage by mass: 0.1wt% of titanium nitride whiskers, 14.5wt% of organic carrier, and 85.4wt% of surface-modified nanocluster ultrafine copper particles.
[0098] The difference between Comparative Example 3 and Example 1 is that a high-reliability low-temperature sintering copper paste is made of the following raw materials in percentage by weight: 6wt% of titanium nitride whiskers, 14.5wt% of organic carrier, and 79.5wt% of surface-modified nanocluster ultrafine copper particles.
[0099] The difference between Comparative Example 4 and Example 5 is that a high-reliability low-temperature sintered copper paste is made of the following raw materials in percentage by mass: 2.5wt% of titanium nitride whiskers, 14.5wt% of organic carrier, 82wt% of ultrafine copper particles with a particle size of 1-3 microns, and 1wt% of nanosilver with an average particle size of 20-80nm (superior grade, model CB2311).
[0100] The difference between Comparative Example 5 and Example 5 is that a high-reliability low-temperature sintered copper paste is made of the following raw materials in percentage by mass: 2.5wt% of titanium nitride whiskers, 14.5wt% of organic carrier, and 83wt% of ultrafine copper particles with a particle size of 1-3 microns.
[0101] Performance test: 1. Shear test: Use a push-pull force tester to perform a shear test on the sintered joint, with a shear height of 15μm and a shear speed of 30μm / min, and record the shear strength data. 2. Thermal conductivity test: Use the laser flash method to detect the thermal diffusion coefficient of the circular sheet sample, the test temperature is room temperature, the pulse width is 20μs, the specific heat capacity and density of the sample are measured, and the thermal conductivity is calculated and recorded. 3. Resistivity test: Use the four-probe method to detect the resistance of the circular sheet sample, the test temperature is room temperature, and then calculate the resistivity according to the formula ρ=2πl(U / I)*F and record it, where ρ is the sample volume resistivity, l is the probe distance, U is the measured potential difference, I is the measured current, and F is the correction factor, which is queried from the correction factor table of the instrument according to the sample thickness h, diameter D and probe spacing l.
[0102] Table 1 Test parameters of interconnection materials prepared by high reliability low temperature sintering copper paste in Examples 1-16 and Comparative Examples 1-5
[0103]
[0104]
[0105] Combining Examples 1-16 and Comparative Examples 1-5 and Table 1, it can be seen that compared with Comparative Examples 1-3, the addition of titanium nitride whiskers can improve the shear strength of the interconnected materials formed by sintering, and can improve the electrical conductivity and thermal conductivity of the interconnected materials formed by sintering. The addition amount of titanium nitride whiskers is preferably controlled at 0.5wt% to 5wt%. Based on the cost and comprehensive performance of industrial production, the addition amount of titanium nitride whiskers is preferably controlled at 1.5wt% to 3.0wt%.
[0106] In combination with Examples 1-16 and Comparative Examples 1-5 and Table 1, it can be seen that, compared with Example 2 and Example 4, the modified titanium nitride whiskers prepared in the present application have a certain effect on improving the shear strength of the interconnected materials formed by sintering, and the electrical conductivity and thermal conductivity of the interconnected materials formed by sintering are significantly improved, which is conducive to the formation of a dense sintered body.
[0107] Combining Examples 1-16 and Comparative Examples 1-5 and Table 1, it can be seen that the shear strength, electrical conductivity and thermal conductivity of the interconnected materials prepared by sintering the ultrafine copper particles of the surface-modified nanoclusters prepared in Examples 2 and Examples 5-6 are relatively superior. It can be seen from the comparison between Examples 2 and Examples 5-6 that the interconnected materials prepared by sintering the ultrafine copper particles of the surface-modified nanoclusters prepared in Example 6 are relatively superior. Based on the cost and comprehensive performance of industrial production, Example 2 is relatively economical.
[0108] Combining Examples 1-16 and Comparative Examples 1-5 and Table 1, it can be seen that the addition of single-atom modified graphene powder can improve the electrical conductivity and thermal conductivity of the interconnected material formed by sintering, and has little effect on the shear strength of the interconnected material. The addition amount of the single-atom modified graphene powder is preferably 0.1wt% to 1.0wt% of the total mass of the surface-modified ultrafine copper particle composition, preferably 0.4wt% to 0.6wt%.
[0109] Combining Examples 1-16 and Comparative Examples 1-5 and Table 1, it can be seen that the addition of PDA@GNP-conductive nanosilver particles can improve the electrical conductivity and thermal conductivity of the interconnected material formed by sintering, and has little effect on the shear strength of the interconnected material. The addition of PDA@GNP-conductive nanosilver particles can further improve the electrical conductivity and thermal conductivity of the interconnected material formed by sintering. The addition amount of PDA@GNP-conductive nanosilver particles accounts for 0.5wt% to 5wt% of the total mass of the surface-modified ultrafine copper particle composition, preferably 2.6wt% to 2.8wt%.
[0110] The high reliability low temperature sintered copper paste in Example 14 was sintered in a nitrogen atmosphere, the sintering temperature was 240°C, the sintering pressure was 10MPa, and the shear strength of the sintered interconnected material could reach 85.8MPa, the resistivity could reach 0.96μΩ·cm, and the thermal conductivity was 231.2W / (m·K). The interconnected joints formed by sintering the high reliability low temperature sintered copper paste in Example 14 were subjected to high and low temperature cycle tests and aging tests. After 1000 cycles, the shear strength of the interconnected joints was 81.6MPa, and after aging at 250°C for 800h, the shear strength of the interconnected joints was 80.8MPa. The high reliability low temperature sintered copper paste in Example 14 was used for reliability testing of MLCC products, and the results are shown as follows: Test item: terminal electrode adhesion, test method: welding leads at both ends to test adhesion through a tensile machine, qualified standard: sample terminal electrode tension ≥ 2LB, test result: qualified. Test item: accelerated life, test method: test in a life test box at 125C, 1.5 times rated voltage, 1000h, qualification standard: sample failure rate ≤0.01%, test result: qualified.
[0111] In summary, the interconnection joints obtained by low-temperature sintering of the high-reliability low-temperature sintered copper paste in this application have excellent sintering strength, high thermal conductivity, high reliability and low resistivity, which meet the connection material requirements of the third-generation wide-bandgap semiconductor WBG, and can realize the electrical, thermal and mechanical connection between the chip surface electrode and the circuit lining, and further meet the application requirements of silicon carbide devices or gallium nitride devices in industries such as electric vehicles, smart grids, and new energy.
[0112] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A high reliability low temperature sintering copper paste, characterized in that: The invention is made of the following raw materials in the following mass percentages: 0.5wt% to 5wt% of titanium nitride whiskers, 10wt% to 25wt% of an organic carrier, and the balance being a surface-modified ultrafine copper particle composition; the organic carrier contains an organosilicon-modified epoxy resin, an organic solvent, a dispersant, a leveling agent, a curing agent, and a coupling agent; the surface-modified ultrafine copper particle composition at least includes ultrafine copper particles with surface-modified nanoclusters.
2. The high reliability low temperature sintering copper paste according to claim 1, characterized in that: The preparation method of the surface-modified nanocluster ultrafine copper particles is as follows: first, 3 to 6 parts of a particle size D 50 =1-3 micron spherical ultrafine copper powder, 3-6 parts of silver nitrate, and 240-300 parts of ethylene glycol are mixed at 300-600 rpm for 100-200 seconds, and then ultrasonic dispersion treatment is performed for 2-4 hours, the obtained dispersion liquid is heated to 138-145° C. at a heating rate of 4-6° C. / min and kept warm for 20-30 minutes, and naturally cooled to room temperature and then centrifuged, and the obtained solid is cleaned with deionized water to obtain ultrafine copper particles with surface modified nanosilver clusters; the particle size of the nanosilver clusters loaded on the surface of the obtained ultrafine copper particles with surface modified nanosilver clusters is 10-20 nm, and the shape of the nanosilver clusters is spherical.
3. The high reliability low temperature sintering copper paste according to claim 1, characterized in that: The preparation method of the surface-modified nanocluster ultrafine copper particles is as follows: 10 parts of a particle size D 50 =1-3 micron spherical ultrafine copper powder, 1-2 parts of nanosilver with an average particle size of 20-80nm, 100 parts of distilled water, and 10-25 parts of ethanol are mixed at 300-600rpm for 300-600s, and then transferred to a planetary ball mill after mixing evenly. The planetary ball mill uses tungsten carbide grinding beads with a diameter of 1-4mm, and high-purity argon is introduced to exhaust the air in the planetary ball mill. After pressurizing to 0.5-0.8MPa, it is ball-milled at 800-1600rpm for 8-12h. After the pressure is released to normal pressure, the obtained ball-milled product is rinsed with distilled water and transferred to a beaker. The obtained ball-milled product is decompressed and filtered to obtain a solid powder. Finally, the obtained solid powder is washed with distilled water for at least three times, and the obtained solid powder is dried at 65-80°C for 4-12h to obtain finished product surface-modified nano-clustered ultrafine copper particles.
4. The high reliability low temperature sintering copper paste according to claim 1, characterized in that: The preparation method of the surface-modified nanocluster ultrafine copper particles is as follows: first, prepare a mixed solution containing nano silver ions, take 30-50 parts of the nano silver ion mixed solution and 10 parts of a particle size D 50 = 1 to 3 micron spherical ultrafine copper powder is mixed at 300 to 600 rpm for 300 to 600 s to obtain a dispersion, the obtained dispersion is filtered, washed, and dried to obtain a solid, the obtained solid is mixed with 100 parts of distilled water and 10 to 25 parts of ethanol at 300 to 600 rpm for 300 to 600 s, and then transferred to a planetary ball mill after mixing evenly. The planetary ball mill uses tungsten carbide grinding beads with a diameter of 1-4 mm, and high-purity argon is introduced to exhaust the air in the planetary ball mill. After pressurizing to 0.5 to 0.8 MPa, it is ball milled at 800 to 1600 rpm for 8 to 12 hours. After the pressure is released to normal pressure, the obtained ball milling product is rinsed with distilled water and transferred to a beaker. The obtained ball milling product is filtered under reduced pressure to obtain a solid powder. Finally, the obtained solid powder is washed with distilled water at least three times, and the obtained solid powder is dried at 65 to 80 ° C for 4 to 12 hours to obtain finished surface-modified nano-clustered ultrafine copper particles.
5. The high reliability low temperature sintering copper paste according to claim 4, characterized in that: The preparation method of the nano silver ion mixed solution is as follows: firstly prepare silver acetate ammonia complex CH3COO(NH3)2Ag, then slowly add formic acid HCOOH to the prepared silver acetate ammonia complex CH3COO(NH3)2Ag, the mass ratio of formic acid HCOOH to silver acetate ammonia complex CH3COO(NH3)2Ag is (18-20): (65-70), stirring is performed while dropping, and the stirring speed is 1000-1500 r / min. After the formic acid HCOOH is added, stirring is continued for 30-60 min and then aged for 12-24h. The obtained mixed solution is heated to 120-150°C at a heating rate of 4-6°C / min and kept warm for 30-60min, and naturally cooled to room temperature to obtain the nano silver ion mixed solution. The obtained nano silver ion mixed solution contains spherical conductive nano silver particles, and the particle size distribution of the obtained spherical conductive nano silver particles is 2-20nm.
6. The high reliability low temperature sintering copper paste according to claim 1, characterized in that: The surface-modified ultrafine copper particle composition at least includes ultrafine copper particles with surface-modified nanoclusters and single-atom modified graphene powder, wherein the single-atom modified graphene powder accounts for 0.1wt% to 1.0wt% of the total mass of the surface-modified ultrafine copper particle composition, and the single-atom modified graphene powder includes a graphene carrier and a transition metal single atom supported on the surface of the graphene carrier; the mass ratio of the transition metal single atom to the graphene carrier is 1:(10-50); and the transition metal single atom is at least one of Cu and Ag.
7. The high reliability low temperature sintering copper paste according to claim 6, characterized in that: The surface-modified ultrafine copper particle composition at least comprises ultrafine copper particles with surface-modified nanoclusters, single-atom modified graphene powder and PDA@GNP-conductive nanosilver particles, wherein the PDA@GNP-conductive nanosilver particles account for 0.5wt% to 5wt% of the total mass of the surface-modified ultrafine copper particle composition.
8. The high reliability low temperature sintering copper paste according to claim 7, characterized in that: The surface of the titanium nitride whisker is fixedly connected with carbon nanotubes CNTs through a connecting material, and the connecting material is a nanosilver sintered body; the preparation method of the titanium nitride whisker surface, The following steps are involved: S1: prepare Ag(2E4MI)2Ac complex solution; S2: add polyvinyl pyrrolidone PVP and CNTs to the Ag(2E4MI)2Ac complex solution, wherein the mass ratio of the polyvinyl pyrrolidone PVP to CNTs is 1:(0.8-1.2), and the mass ratio of the Ag(2E4MI)2Ac complex solution to the polyvinyl pyrrolidone PVP is (350-500):1, and then ultrasonically disperse for 4-6 hours, add matrix titanium nitride whiskers, wherein the diameter of the matrix titanium nitride whiskers is 0 .5~1.0um, length is 10~20um, the mass ratio of the titanium nitride whisker to polyvinyl pyrrolidone PVP is (8~12): 1, after the titanium nitride whisker is added, ultrasonic dispersion is performed for 1-2h to obtain a dispersion; S3, the obtained dispersion is subjected to reduced pressure distillation to remove the organic solvent in the Ag(2E4MI)2Ac complex solution, and the solid is subjected to high-temperature sintering treatment, the sintering temperature is 200-220℃, the obtained solid is crushed, dispersed in ethanol, ground, filtered, and dried to obtain the finished titanium nitride whisker.
9. A high reliability low temperature sintering copper paste as claimed in any one of claims 1 to 8, used as a semiconductor packaging interconnection material in the electronic industry.
10. A high-reliability, low-temperature sintered copper paste according to any one of claims 1 to 8 is used for packaging interconnection material electronic paste of third-generation semiconductor WBG materials to achieve electrical, thermal and mechanical connection between chip surface electrodes and circuit substrates.
Citation Information
Patent Citations
Pressureless sintered conductive silver paste and preparation method thereof
CN108053916A
Method of Fabricating High-Conductivity Thick-film Copper Paste Coated with Nano-Silver for Being Sintered in the Air
US20170218512A1